Alcohol Use And Risk Sexual Behaviours Among Soldiers At Field Airforce Base: An Implication for Hiv/Aids Prevention - Vidza, Rumbidzai (Midlands State University, 2017)
Alcohol use and risk sexual behaviour is a global burden that is taking on the health systems and economic development world over in terms of the consequences and risks that it poses. The purpose of this study was to reconnoitre the predicament of alcohol use by soldiers so as to acquire knowledge about alcohol use and risk sexual behaviours that may consequently lead to ill health and other negative effects for the problem to be reduced or curbed or better yet prevented. The versatile environment of the military leaves soldiers vulnerable from time to time that they resort to alcohol use and subsequently sexual indulgence as a coping strategy. Alcohol use and risk sexual indulgence may also pose a threat of jeopardising HIV/AIDS prevention and promotion of sexual health. A quantitative approach which employed the use of descriptive survey to research was adopted in this paper to describe current situations and conditions. Data collection took the form of questionnaires administered within the various messes and sections. The sample was 196 participants derived across the ranks. The data analysis employed descriptive statistics that saw demographics presented in frequency whilst association of variables employed chi-square tests using the Statistical package in Social Sciences version 20. The research found out that at more than half the sample were alcohol users and had engaged in risk sexual behaviours at some point in their lives. The research generated evidence that there was a significant association between alcohol use and risk sexual behaviours and therefore recommendations to mitigate the peril were put.